Implementasi manajemen pembelajaran dalam upaya meningkatkan mutu hasil pendidikan di SMP Terbuka 4 Pandak Bantul - Waluya Waluya (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
This study aims to describe the implementation of learning management including planning, implementation, and evaluation of open school teachers, to explain how learning management can improve the quality of education outcomes, and to describe the obstacles encountered in the implementation of learning management in improving the outcomes of education in Open Junior High School 4 Pandak Bantul Yogyakarta. This research is a qualitative descriptive study. The research instruments used in this research were interview guidelines, observation guidelines, and document checklists. The analysis of data was done by descriptive and qualitative analysis. The validity of the data was done by a triangulation technique. The research results showed that in general, the learning management can improve the quality of education of Open Junior High School 4 Pandak, Bantul, Yogyakarta. The complete results were (1) the learning management in Open Junior High School 4 Pandak, Bantul, Yogyakarta has been implemented procedurally following the stages of planning, implementation, evaluation, and follow-up; (2) the implementation of learning management gave contribution in improving the quality of education; (3) some obstacles or barriers related to the implementation of learning management derived from the open school teachers, the principal, and the school staffs; (4) the solution to overcome the obstacles was giving motivation and conducting good coordination among the open school teachers, principal, and school staffs.